2006
DOI: 10.2174/1389450110607011539
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System in Ageing: A New Target for Drug Development

Abstract: Endocannabinoids are a new class of lipids, which include amides, esters and ethers of long chain polyunsaturated fatty acids. Anandamide (N-arachidonoylethanolamine; AEA) and 2-arachidonoylglycerol are the main endogenous agonists of cannabinoid receptors able to mimic several pharmacological effects of Delta(9)-tetrahydrocannabinol, the active principle of Cannabis sativa preparations like hashish and marijuana. AEA is released "on demand" from membrane lipids, and its activity at the receptors is limited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 168 publications
1
21
0
Order By: Relevance
“…Whereas the PE pressor method measures BRS after evoked changes in AP in an open-loop system, the spontaneous method measures changes in a closed-loop model over a much smaller (beat-to-beat) range, although a highly significant correlation exists between them (16). Collectively, blockade of endocannabinoid actions at NTS CB 1 receptors improved blood pressure regulation in older SD rats as assessed using several indices of BRS and sympathovagal function, consistent with upregulated systemic CB 1 receptor tone during conditions associated with aging including hypertension (6) and metabolic syndrome (5). …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Whereas the PE pressor method measures BRS after evoked changes in AP in an open-loop system, the spontaneous method measures changes in a closed-loop model over a much smaller (beat-to-beat) range, although a highly significant correlation exists between them (16). Collectively, blockade of endocannabinoid actions at NTS CB 1 receptors improved blood pressure regulation in older SD rats as assessed using several indices of BRS and sympathovagal function, consistent with upregulated systemic CB 1 receptor tone during conditions associated with aging including hypertension (6) and metabolic syndrome (5). …”
Section: Discussionmentioning
confidence: 67%
“…Alterations in the brain endocannabinoid system that accompany age-related cognitive decline (4), cardiovascular diseases or metabolic disorders (5) may contribute to the modulation of baroreflex function during aging. The endocannabinoid system is a central and peripheral cellular signaling system that comprises the endogenous cannabinoids anandamide and 2-arachidonoylglycerol (2-AG), their G protein-coupled CB 1 and CB 2 receptor subtypes, and enzymes regulating their biosynthesis and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the ECS is known to play a key role in pathological events occurring in the AD brain: excitotoxicity [12], oxidative stress [13] and inflammation [2]. Yet, few studies investigated alterations of the ECS in normal or pathological aging (reviewed in Paradisi et al [14]). For example, it has been reported that CB 1 receptors are decreased in aged rats [15], [16] and in human pathological conditions affecting basal ganglia structures [17], and CB 1 receptor in human AD brains mainly demonstrates no changes [18], [19], [20] or decreased levels [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…Marijuana is a well-known recreational drug that has for centuries been prescribed therapeutically in herbal medicine for the treatment of many disorders, including loss of appetite [1]. The identification of the major active constituent of marijuana, Δ 9 -THC [2], followed by the biochemical and pharmacological characterization of the cannabinoid receptors [3,4], provided a solid foundation and opened a new perspectives for the study of this neurochemical system [5].…”
Section: Introductionmentioning
confidence: 99%